The Role Of IL-6 In TMPD-Treated Lupus Arthritis Mice - Indriyanti, Niken (KnE Life Sciences, 2017)
Lupus or systemic lupus erythematosus is a chronic autoimmune disease with systemic inflammation manifestations mainly in targeted organs. The appropriate animal model for lupus is necessary. The induction method by using 2,6,10,14 tetramethylpentadecane (TMPD) reveals more complex manifestations than other hydrocarbons. However, the autophagy of macrophages as an effect of TMPD makes differences to make the decision in lupus biomarker as a targeted therapy in lupus arthritis. Thus, this research focused on the role of CD68+IL-6 produced by macrophages and total IL-6 in lupus in correlation to the arthritis severity. The naïve and TMPD-treated groups (n=3) were induced by means of 0.5 ml TMPD i.p. After 6 months, the mice were sacrificed then the fresh spleens were prepared as isolated cells to be measured by using flow cytometry method. The knee joints were prepared for histology observation. The statistical analysis was performed by using T-test SPSS 22 version. The results showed the relative percentage of CD68+IL-6+ in the TMPD-treated group increased significantly (P<0.05) with the value of 62.38±9.97 %, compared to naïve group 49.70±2.34 %. Moreover, the total IL-6 did not increase significantly (P>0.05). Meanwhile, the arthritis severity score of the TMPD-treated group revealed severe erosion with the grade of 3.7±1.06, higher significantly (P<0.05) than the naïve group (0.5±0.71). The joint spaces in both groups were not significantly different. Finally, the observations gave the clear information that despite the autophagy potency, the CD68+IL-6 and the arthritis severity score were good markers in lupus preclinical study. Keywords: CD68+IL-6; inflammation; lupus arthritis; TMPD